Development of a novel hybrid method combining finite difference method and dissipative particle dynamics to simulate thrombus formation on orifice flow. Issue 10 (26th July 2020) - Yi, Y.; Tamagawa, M.
Abstract: In our previous works, the transport of activated platelets (APs) on orifice flow has been simulated by finite difference method (FDM). And the distribution of AP concentration on the flow was obtained. However, the effect of platelet aggregation on the distribution of AP concentration can't be investigated by FDM because FDM can't simulate platelet aggregation. On the other hand, platelet aggregation has been simulated by dissipative particle dynamics (DPD). In this paper, a hybrid method combining FDM and DPD is proposed to investigate the effect of platelet aggregation on the distribution of AP concentration. And the hybrid method is used to simulate thrombus formation on orifice flow. As for the effect of platelet aggregation, it is found that the distribution of AP concentration in the hybrid method is different from the distribution in FDM at the places of platelet aggregation. It is considered that the difference is induced by platelet aggregation. As for the distribution of thrombus, higher AP concentration and more aggregated APs are found around the reattachment point and in the recirculation area. It is considered that thrombus is mainly distributed at these places in the simulation. And according to our previous experimental results, thrombus is mainly distributed around the reattachment point and in the recirculation area. It is concluded that the effect of platelet aggregation on the distribution of AP concentration can be investigated by the hybrid method, and the computational results agree with our previous experimental results.